BIOLOGICAL CONTROL OF FOOT AND ROOT ROT DISEASE OF PEA BY USING FORMULATED PRODUCT OF Trichoderma - Karim, Fatima; Hossain, Sk. Md. Mobarak; Hasan, Md. Mahfuzul; Howlader, Nayan Chandra; Bhuiyan, Mohd Mujtaba Akib (Journal of Agricultural Sciences (Belgrade), 2024)
Fusarium oxysporum and Sclerotium rolfsii are principally accountable foot and root rot diease of pea. Trichoderma is a filamentous fungus in the class Ascomycota and order Hypocreales that grows in soil, wood, plant materials, and rotting plants. The Plant Pathology Research plot of Hajee Mohammad Danesh Science and Technology University, Dinajpur, Bangladesh conducted this randomized complete block design investigation to test Trichoderma group’s fungicide for pea foot and root rot control. Five bio-fungicidal treatments of Trichoderma group-Decoprima (T2), Lycomax (T3), Dynamic (T4), Tricost (T5), Provax 200 (T6), Trichoderma (T7), and Provax 200 (T6)-were used to compare results to untreated control plots. Lycomax (T3) was well in suppressing pea foot and root rot disease and other growth metrics across many dates. Lycomax (T3) gave the highest yield (39.81 g/plot) at 92 days after sowing compared to other treatments and untreated plots (11.67 g/plot). Although the chemical treatment Provax 200 (T6) controlled pea foot and root rot disease and yielded 33.76 g/plot, it is not eco-friendly. Lycomax (T3) had the greatest results at 75 days after sowing in all metrics, including number of surviving seedlings (64.67/plot), lowest number of infected plants (4/plot), plant height (67.33 cm/plot), and number of root branches/plant (33.33/plot). Lycomax (T3) treated plot at 82 days after sowing had the most root length (28.33 cm/plot), number of root nodules (30.33/plant/plot), and branches (33.33/plant/plot). Flowers (76/plot) and pods (12.33/plot) peaked at 65 and 75 days after sowing. The current study demonstrated that Lycomax (generic name: Trichoderma) is the best bio-fungicide to treat pea foot and root rot disease in an eco-friendly manner and boost production by increasing plant health. The trial promotes field usage of Lycomax, a bio-fungicide.